CO2 capture from dry flue gas by pressure vacuum swing adsorption: A systematic simulation and optimization. (August 2016) - Yan, Haiyu; Fu, Qiang; Zhou, Yan; Li, Dongdong; Zhang, Donghui
Highlights: A novel two-bed, one-stage PVSA system that used to capture and concentrate CO2 from dry flue gas was simulated, experimented and optimized. The r-SQP algorithm is employed to optimize design variables to minimize the unit energy consumption. Performances of simulative cyclic steady state and optimal conditions are compared to show the advantages of process optimization on VPSA process improvement. Abstract: A vacuum pressure swing adsorption process that used silica gel as adsorbent to capture CO2 from dry flue gas (85%N2 /15%CO2 ) by two-bed one-stage operation is investigated through dynamic simulation and optimization. Heavy component purge is added into schedule to improve the concentration of CO2 and light product of this step is collected and utilized for pressurization to save energy and guarantee a handsome recovery. Models of bed and sub-units all established in gPROMS and the accuracy of simulation results is verified by experiments. To decrease the energy consumption of the process, decision variables are optimized by r-SQP method within given constraints. Results show that under optimal conditions, the purity of CO2 could reach 90.77% with recovery of 76.47% and energy consumption reduced from 623.64 kWh tonne −1 at simulation to 419.99 kWh tonne −1 under optimal condition. Distribution of CO2 at the end of each step under optimal condition is given on both gas and solid phase with comparison of initial state to insight the effects of operation and decision variables on the whole VPSA process.